Synergistic effects of bioagents and botanicals for integrated management of rice root-knot nematode (Meloidogyne graminicola) - WAGHMARE, CHANDRAMANI D; PANKAJ; PERVEZ, RASHID (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during rainy (kharif) seasons of 2023 and 2024 at ICAR-Indian Agricultural Research Institute, New Delhi to investigate the efficacy of multiple treatment methods in controlling rice root-knot nematode (Meloidogyne graminicola), under field conditions. The treatments tested included the nematicide Fluensulfone (trade name Nimitz) @5 g/block, bioagent Bacillus subtilis @15 g/plot (CFU 1.5 × 109), and the botanicals garlic oil @2000 ppm and annona oil @20000 ppm, and were applied separately and in combination. The experiment was conducted with and without polythene sheet covering. All the observations were made at 60 days’ post-treatment, focusing on plant height and the number of galls/seedling. Results showed that the combined application of garlic oil and B. subtilis significantly reduced nematode infestation, with the lowest gall count (9.14/plant) and the tallest seedlings (48.8 cm), especially under polythene sheet covering. Similar patterns were observed with other combinations of garlic oil and subtilis, showing notable increase in plant height and decrease in gall counts. The influence was more significant with polythene covering compared to without polythene sheet covering.